Age, Creatinine and Ejection Fraction Score in Brazil: Comparison with InsCor and the EuroSCORE - Mejía,Omar Asdrúbal Vilca (2015)
AbstractBackground:Risk scores for cardiac surgery cannot continue to be neglected.Objective:To assess the performance of “Age, Creatinine and Ejection Fraction Score” (ACEF Score) to predict mortality in patients submitted to elective coronary artery bypass graft and/or heart valve surgery, and to compare it to other scores.Methods:A prospective cohort study was carried out with the database of a Brazilian tertiary care center. A total of 2,565 patients submitted to elective surgeries between May 2007 and July 2009 were assessed. For a more detailed analysis, the ACEF Score performance was compared to the InsCor’s and EuroSCORE’s performance through correlation, calibration and discrimination tests.Results:Patients were stratified into mild, moderate and severe for all models. Calibration was inadequate for ACEF Score (p = 0.046) and adequate for InsCor (p = 0.460) and EuroSCORE (p = 0.750). As for discrimination, the area under the ROC curve was questionable for the ACEF Score (0.625) and adequate for InsCor (0.744) and EuroSCORE (0.763).Conclusion:Although simple to use and practical, the ACEF Score, unlike InsCor and EuroSCORE, was not accurate for predicting mortality in patients submitted to elective coronary artery bypass graft and/or heart valve surgery in a Brazilian tertiary care center. (Arq Bras Cardiol. 2015; [online].ahead print, PP.0-0)